Implementasi Manajemen Risiko Penularan Covid-19 terhadap Perawat Indonesia di Kuwait melalui Metode Bowtie - I Gede Swastama Putra; Iman Basriman Basriman; Sugiarto Sugiarto (Penerbit Goodwood, 2023)
Purpose: The purpose of this service is to obtain an overview of the implementation of COVID-19 transmission risk management for Indonesian nurses working in Kuwait through the Bowtie method. Methodology: This research is quantitative in nature using a scientific approach to the implementation of risk management for the transmission of COVID-19 in Indonesian nurses working in Kuwait where these nurses work in various health services in Kuwait. This research was conducted using a descriptive analytic method using a cross-sectional study design. Result: The results of the study found that: 1) The application of risk management (risk control or mitigation) in handling COVID-19 in various health services in Kuwait such as the implementation of hospitalization for staff who were confirmed positive and the existence of a COVID-19 vaccination program had a significant effect on the transmission of COVID-19 -19 in Indonesian Nurses working in Kuwait. 2) The level of knowledge about the importance of preventing and transmitting COVID-19 to Indonesian nurses in Kuwait has a very significant influence on the transmission of COVID-19. 3) The level of compliance of Indonesian nurses with infection prevention control measures or health protocols has a significant effect on the transmission of COVID-19 in Indonesian nurses working in various health services in Kuwait.